Md. Act for the Liberties of the People (1639) - (:unkn) unknown (General Publisher, 1639)
Gave the inhabitants of Maryland, who are Christians, all rights, liberties, immunities, priviledges, and free customs as naturally born Englishmen.
--
Keywords: GUARANTEED RIGHT